Badania kliniczne i doświadczalne w chorobach serca, płuc i naczyńNew guidelines of the American Diabetes Association (ADA) emphasize the diagnostic and prognostic value of glycated haemoglobin: reasons for satisfaction for cardiac surgeons and the operated patients - Trzeciak, Przemysław; Foremny, Jerzy; Wróbel, Marta; Herdyńska-Wąs, Mirosława; Hrapkowicz, Tomasz; Szymborska-Kajanek, Aleksandra; Nadziakiewicz, Paweł; Knapik, Piotr; Kucewicz, Ewa; Strojek, Krzysztof; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The latest published guidelines of the American Diabetes Association (ADA) for the first time introduce the assessment of glycated haemoglobin percentage (HbA1c) as a tool in diagnosing advanced diabetes. According to the guidelines, diabetes may be diagnosed when the HbA1C value is equal to or greater than 6.5%. The guidelines still include the diagnostic criteria based on the fasting glycemic level (≥ 126 mg/dl) and glycemic results two hours after oral administration of 75 γ of glucose (≥ 200 mg/dl). The work outlines the preparation of diabetic patients with elevated glycated haemoglobin, qualified for cardiac surgeries. The different courses of action in patients qualified for elective and non-elective surgery are demonstrated, and the rules on incorporating insulin into the therapy are discussed. Furthermore, the article describes the schedule of intravenous continuous insulinotherapy in the perioperative period, implemented in patients undergoing cardiac surgeries at the Silesian Centre for Heart Diseases in Zabrze since 2002.